2021
DOI: 10.1177/10556656211067120
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Orthognathic Surgery in Patients with Cleft: An Overview of Available Patient-Reported Outcome Measures

Abstract: Measuring the impact of orthognathic surgery on quality of life is of significant importance in patients with cleft deformities. Standardized tools such as patient-reported outcome measures (PROMs) are needed to fully comprehend patients’ needs and perceptions. Therefore, the availability of reliable, valid, and comprehensive questionnaires for patients is essential. The aim of this study is to identify PROMs measuring the impact of orthognathic surgery on quality of life in patients with cleft deformities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…6 However, in previous research, the psychological assessment of youths with CL/P has usually been conducted using instruments developed for nonaffected youths (eg, the Strengths and Difficulties Questionnaire, the Satisfaction with Appearance scale, and the Self-Perception Profile for Adolescents). While recent research has reported some validated instruments for youth with CL/P, such as the PAT-CV or CleftQ, 19,20 the specific issues concerning the impact of living with a facial difference-as perceived by the youths themselves-have not been well studied. 2 To focus on this issue, the Youth Quality of Life Instrument-Facial Differences Module (YQOL-FD) was developed by Patrick et al, 2 Edwards et al, 21 and Topolski et al 22 This instrument is designed to evaluate the quality of life (QoL) of youths with both congenital and acquired facial differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, in previous research, the psychological assessment of youths with CL/P has usually been conducted using instruments developed for nonaffected youths (eg, the Strengths and Difficulties Questionnaire, the Satisfaction with Appearance scale, and the Self-Perception Profile for Adolescents). While recent research has reported some validated instruments for youth with CL/P, such as the PAT-CV or CleftQ, 19,20 the specific issues concerning the impact of living with a facial difference-as perceived by the youths themselves-have not been well studied. 2 To focus on this issue, the Youth Quality of Life Instrument-Facial Differences Module (YQOL-FD) was developed by Patrick et al, 2 Edwards et al, 21 and Topolski et al 22 This instrument is designed to evaluate the quality of life (QoL) of youths with both congenital and acquired facial differences.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, in previous research, the psychological assessment of youths with CL/P has usually been conducted using instruments developed for nonaffected youths (eg, the Strengths and Difficulties Questionnaire, the Satisfaction with Appearance scale, and the Self-Perception Profile for Adolescents). While recent research has reported some validated instruments for youth with CL/P, such as the PAT-CV or CleftQ, 19,20 the specific issues concerning the impact of living with a facial difference—as perceived by the youths themselves—have not been well studied. 2…”
Section: Introductionmentioning
confidence: 99%
“…At the time of this writing, CLEFT-Q was the only validated measurement tool to assess PROs with CLP, and it could be applied in an international and cross-cultural setting. 15 When assessed individually by specific surgical movements, this relationship finds SNA and convexity to explain > 86% of the variability in CLEFT-Q scores for Speech and Distress. Similarly, ANB and Wits appraisal are over 76% predictive for Psychological and Social, whereas maxillary depth correlates to 86% of Eating and Drinking scores.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to clinician-reported outcomes, PROs have become increasingly relevant to assess patient quality of life and satisfaction as a result of orthognathic surgery. 15 Esthetics of a patient's physical appearance and facial function are usually a patient's top priority after completing orthognathic surgery. 16 By synthesizing the data from the CLEFT-Q self-reported outcomes and the clinician surveys, this article aims to gain an objective insight into these qualitative findings by correlating them with surgical movements and cephalometric measurements.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Several patient-reported outcome measures, such as the Satisfaction With Life Scale and Psychosocial Impact of Dental Aesthetics Questionnaire, have been used for patients with CL/P in clinical practice. [13][14][15][16][17] Mainly designed for other patient groups, these instruments are not specific enough to capture all aspects of health-related quality of life in patients with CL/P. 13,18 In Finland, for example, a non-validated questionnaire with 15 items is currently used for measuring the impact of the cleft and cleft treatments in patients with CL/P.…”
Section: Introductionmentioning
confidence: 99%